Spectrophotometric Study of Charge-Transfer Complexes of Ruxolitinib with Chloranilic Acid and 2,3-Dichloro-5,6-dicyano-1,4-benzoquinone: An Application to the Development of a Green and High-Throughput Microwell Method for Quantification of Ruxolitinib in Its Pharmaceutical Formulations - Khalid A. Aljaber; Ibrahim A. Darwish; Abdullah M. Al-Hossaini (Molecules, 2023)
Ruxolitinib (RUX) is a potent drug that has been approved by the Food and Drug Administration for the treatment of myelofibrosis, polycythemia vera, and graft-versus-host disease. This study describes the formation of colored charge-transfer complexes (CTCs) of RUX, an electron donor, with chloranilic acid (CLA) and 2,3-dichloro-5,6-dicyano-1,4-benzoquinone (DDQ), the π-electron acceptors. The CTCs were characterized using UV-visible spectrophotometry. The formation of CTCs in methanol was confirmed via formation of new absorption bands with maximum absorption at 530 and 470 nm for CTCs with CLA and DDQ, respectively. The molar absorptivity and other physicochemical and electronic properties of CTCs were determined. The molar ratio was found to be 1:1 for both CTCs with CLA and CTCs with DDQ. The site of interaction on RUX molecules was assigned and the mechanisms of the reactions were postulated. The reactions were employed as basis for the development of a novel green and one-step microwell spectrophotometric method (MW-SPM) for high-throughput quantitation of RUX. Reactions of RUX with CLA and DDQ were carried out in 96-well transparent plates, and the absorbances of the colored CTCs were measured by an absorbance microplate reader. The MW-SPM was validated according to the ICH guidelines. The limits of quantitation were 7.5 and 12.6 µg/mL for the methods involving reactions with CLA and DDQ, respectively. The method was applied with great reliability to the quantitation of RUX content in Jakavi® tablets and Opzelura® cream. The greenness of the MW-SPM was assessed by three different metric tools, and the results proved that the method fulfills the requirements of green analytical approaches. In addition, the one-step reactions and simultaneous handling of a large number of samples with micro-volumes using the proposed method enables the high-throughput analysis. In conclusion, this study describes the first MW-SPM, a valuable analytical tool for the quality control of pharmaceutical formulations of RUX.